Fault Diagnosis in Medium Voltage Drive Based on Combination of Wavelet transform and Support Vector Machine - Xudong Cao; Shaozhe Zhou; Jingze Li; Shaohua Zhang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Nowadays, Medium Voltage Drive (MVD) has been widely applied in the field of high-powered motor speed-regulation. These types of converter use a lot of insulated gate bipolar translators (IGBTs). So it is very important to find an effective way to diagnose IGBT open-circuit faults. This study describes a method of diagnosis for IGBT open-circuit faults in MVD whose topology is cell series of multi-level. This method combines wavelet transform (WT) and support vector machine (SVM). The wavelet transform is used to extract fault features and SVM is used to classify the fault states of a single power unit. Then, the trained SVM classifier is used to scan all power units of MVD sequentially. Results of simulation on the platform of MATLAB/Simulink show that this method has a good diagnosis capability. It can diagnose the IGBT open-circuit faults of the whole inverter system, and diagnosis accuracy is up to 96%. So, this method has a good application prospect.